Patterns of fetal growth based on ultrasound measurement and its relationship with small for gestational age at birth in rural Vietnam - Nguyen, Phuong Hong; Addo, O. Yaw; Young, Melissa; Gonzalez-Casanova, Ines; Pham, Hoa; Truong, Truong V.; Nguyen, Son; Martorell, Reynaldo; Ramakrishnan, Usha (Wiley, 2016)
Small for gestational age (SGA) is a global health problem. Identifying the timing of fetal growth faltering is critical for developing preventive interventions. We aim to describe patterns of fetal growth and to predict SGA at birth using fetal ultrasound measurements.We studied 1412 pregnant women enrolled in a randomised‐controlled trial evaluating maternal micronutrient supplementation in Thai Nguyen province, Vietnam. Ultrasound examinations included biparietal diameter (BPD), head circumference (HC) and abdominal circumference (AC), and femur length (FL). Measures were assessed using the new international fetal growth standards (INTERGROWTH‐21st Project). Generalised linear mixed logit regression models were used to examine the association between ultrasound measures and SGA at birth.Overall fetal growth restriction began in early pregnancy and continued through delivery, but the timing of growth faltering varied by measure: it began by 20 weeks for HC, BPD and AC, earlier as compared to FL growth that started >30 weeks. SGA infants had significantly lower mean fetal growth parameters as early as 14 weeks. Ultrasound measures below the 10th percentile were associated with a two to four times higher risk of SGA at birth compared to fetuses greater than the 50th percentile, with the largest odds ratios for AC (OR 3.9, 95% confidence interval (CI) 2.7, 5.7).Fetal growth faltering by ultrasound begins in early gestation among rural Vietnamese populations; these patterns clearly identified those to be born SGA. Efforts to prevent fetal growth faltering must begin early in pregnancy and perhaps even before pregnancy.